Microplastic Pollution: An Emerging Threat to Terrestrial Plants and Insights into Its Remediation Strategies - Arpna Kumari; Vishnu D. Rajput; Saglara S. Mandzhieva; Sneh Rajput; Tatiana Minkina; Rajanbir Kaur; Svetlana Sushkova; Poonam Kumari; Anuj Ranjan; Valery P. Kalinitchenko; Alexey P. Glinushkin (Plants, 2022)
Microplastics (MPs) are ubiquitous and constitute a global hazard to the environment because of their robustness, resilience, and long-term presence in the ecosystem. For now, the majority of research has primarily focused on marine and freshwater ecosystems, with just a small amount of attention towards the terrestrial ecosystems. Although terrestrial ecosystems are recognized as the origins and routes for MPs to reach the sea, there is a paucity of knowledge about these ecological compartments, which is necessary for conducting effective ecological risk assessments. Moreover, because of their high persistence and widespread usage in agriculture, agribusiness, and allied sectors, the presence of MPs in arable soils is undoubtedly an undeniable and severe concern. Consequently, in the recent decade, the potential risk of MPs in food production, as well as their impact on plant growth and development, has received a great deal of interest. Thus, a thorough understanding of the fate and risks MPs, as well as prospective removal procedures for safe and viable agricultural operations in real-world circumstances, are urgently needed. Therefore, the current review is proposed to highlight the potential sources and interactions of MPs with agroecosystems and plants, along with their remediation strategies.